2009
DOI: 10.1007/s10530-009-9534-0
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the invading gastropod Rapana venosa in Punta del Este, Maldonado Bay, Uruguay

Abstract: We report on the first sightings of the invasive Rapa Whelk Rapana venosa in Maldonado Bay (Punta del Este Harbor and Gorriti Island) using in vivo, underwater observations and video surveys. The species was first detected in the Río de la Plata (Uruguay and Argentina) in 1999, and by 2004 it had extended its local distribution to Punta del Este at the eastern boundary of the estuary. Observations performed by SCUBA diving showed that R. venosa is preying on native mussels Mytilus edulis and Brachidontes spp.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 8 publications
2
14
0
3
Order By: Relevance
“…In the same way, competition for marine resources could explain the negative impact of R. venosa on the fleets. In this context, the expansion of R. venosa could be considered a threat for natural resources in the area, as has been suggested previously (Lanfranconi et al 2009;Carranza et al 2010), with possible economic repercussions. The modelled effects of R. venosa in the Río de la Plata region were similar to those recorded in the Chesapeake Bay (Harding and Mann 1999) and indicated a high preference for subtidal mollusks.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In the same way, competition for marine resources could explain the negative impact of R. venosa on the fleets. In this context, the expansion of R. venosa could be considered a threat for natural resources in the area, as has been suggested previously (Lanfranconi et al 2009;Carranza et al 2010), with possible economic repercussions. The modelled effects of R. venosa in the Río de la Plata region were similar to those recorded in the Chesapeake Bay (Harding and Mann 1999) and indicated a high preference for subtidal mollusks.…”
Section: Discussionmentioning
confidence: 56%
“…The modelled effects of R. venosa in the Río de la Plata region were similar to those recorded in the Chesapeake Bay (Harding and Mann 1999) and indicated a high preference for subtidal mollusks. Recently, Carranza et al (2010) showed that R. venosa preys on the native mussels Mytilus edulis and Brachidontes spp. in the Uruguay Atlantic coast (Maldonado Bay), and the formerly abundant mussel beds are being seriously depleted due to a combination of human extraction, habitat deterioration and predation by R. venosa.…”
Section: Discussionmentioning
confidence: 99%
“…10,no. 4 (Muller, 1774) and Rapana venosa (Valenciennes, 1846) that are present in Uruguay have a significant impact on biodiversity at global, regional and local scales (Scarabino 2004, Karatayev et al 2007, Carranza et al 2009, Lanfranconi et al 2009). With regard to tetrapod vertebrates, birds and mammals are the most represented groups in InBUy, with nine species each one (Figure 4).…”
Section: Inbuy Databasementioning
confidence: 99%
“…This species has been shown to be widespread in the area, reaching very high densities all along the Río de la Plata estuary, both in hard and soft bottoms (Scarabino et al 2006;Giberto et al 2006;Lafranconi et al 2009;Carranza et al 2010), and is a threat to native bivalves (e.g. the blue mussel Mytilus edulis; Carranza et al 2010;Scarabino et al 1999). However, the rapa whelks also constitute an important dietary item for immature loggerheads (Caretta caretta) in the Río de la Plata estuary (Carranza et al 2011).…”
Section: Introductionmentioning
confidence: 99%